2022
DOI: 10.3389/fphar.2022.888280
|View full text |Cite
|
Sign up to set email alerts
|

The Antifibrotic and the Anticarcinogenic Activity of Capsaicin in Hot Chili Pepper in Relation to Oral Submucous Fibrosis

Abstract: A burning sensation on eating spicy foods purportedly supports the role of capsaicin, an active component of chili peppers, in the etiology of oral submucous fibrosis (OSF). Although the mast cell mediators and activated P2X receptors induce a constant burning sensation through an ATP-dependent mechanism, it is the activation of the transient receptor potential vanilloid 1 (TRPV-1) receptor by capsaicin that aggravates it. The molecular basis for the burning pain in OSF is thus attributable to the activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Significantly, the outcomes of this study underscore the effectiveness of Capsaicin treatment in improving the macroscopic lung characteristics as well as the histopathological distortions induced by Bleomycin in a comparable and even more substantial restorative effect when compared to the commercially available antifibrotic drug, Pirfenidone. These effects can be attributed to the anti-inflammatory and antifibrotic properties of Capsaicin ( Huang et al, 2022 ; Mansouri et al, 2023 ), which were further highlighted through the assessment of fibrotic and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, the outcomes of this study underscore the effectiveness of Capsaicin treatment in improving the macroscopic lung characteristics as well as the histopathological distortions induced by Bleomycin in a comparable and even more substantial restorative effect when compared to the commercially available antifibrotic drug, Pirfenidone. These effects can be attributed to the anti-inflammatory and antifibrotic properties of Capsaicin ( Huang et al, 2022 ; Mansouri et al, 2023 ), which were further highlighted through the assessment of fibrotic and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although animal studies have indicated few or no side effects of capsaicin, it can irritate the skin of humans and excessive ingestion can cause nausea, vomiting, abdominal pain and burning diarrhea ( 99 ). Contact of capsaicin with eyes can cause severe tearing, pain, conjunctivitis, eyelid spasms and it can trigger mucosal irritation leading to serious gastritis and diarrhea.…”
Section: Pharmacokinetics Of Capsaicinmentioning
confidence: 99%
“…Experimental evidence indicates that capsaicin can reduce fibrosis accumulation on different organs [68]. In two different mouse models of renal fibrosis [69], capsaicin administration reduced fibronectin and collagen depositions in kidneys with a complex action on intracellular signals pathways, involving the inhibition of the Transforming Growth Factor-β1 small mother against decapentaplegic 2/3 signaling, which is the main promoter of profibrotic mechanisms.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%